Risk of mortality: the relationship with associated injuries and fracture treatment methods in patients with unilateral or bilateral femoral shaft fractures. - Willett, K; Al-Khateeb, H; Kotnis, R; Bouamra, O; Lecky, F (2010)
BACKGROUND: The aim of the study was to determine the relative contributions to mortality of a unilateral or a bilateral femoral fracture in patients with or without injuries to other body regions. STUDY DESIGN: An observational cohort study of the prospectively recorded England and Wales Trauma Registry data (Trauma Audit Research Network) from 1989 to 2003. METHODS: Patients were divided into the following groups: UFi (isolated unilateral femur injury), BFi (isolated bilateral femur injury), and UFa and BFa, if an associated injury was present. Injury and treatment data were collected for each patient. Logistic regression data analysis was performed to determine variables that were associated with increased mortality. RESULTS: Patients in group BFa had an increased mortality rate (31.6% vs. 9.8%) than patients in isolated bilateral femur injury group. Group BFa patients had an increased number of associated injuries (80%) than group UFa patients. Bilateral fracture, even in isolation, significantly increased the odds of mortality by 3.07. Intramedullary nailing was the method of fracture fixation associated with the lowest patient mortality overall. When assessing patient mortality in the BFa group with an New Injury Severity Score of >40, seven other fracture fixation regimens were associated with a lower mortality. CONCLUSIONS: The increase in mortality with BFs is more closely associated with the presence of associated injuries and poor physiologic parameters than with the presence of the BF alone. The presence of BFs should alert the clinician to the very high likelihood (80%) of significant associated injuries in other body systems and their life-threatening potential. Damage control fixation options should be considered in the subgroup with a very high New Injury Severity Score.